Education Level and Achievement Motivation Mediated by Job Satisfaction in Developing Nurses Performance at Moh. Ridwan Meuraksa General Hospital - Yohanes Ferry Cahaya; Herni Pujiati; Santi Dwi Jayanti; Annathasia Puji Erasashanti; Theresia Oktavia Sadipung (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2025)
Nursing performance remains critical to quality healthcare delivery, yet the mechanisms through which education level and achievement motivation influence performance outcomes remain understudied. This study examines the mediating role of job satisfaction in the relationships between education level, achievement motivation, and nurse performance at Moh. Ridwan General Hospital, Meuraksa. A cross-sectional study was conducted with 250 nurses using Smart PLS-SEM analysis. Data were collected through validated questionnaires measuring education level, achievement motivation, job satisfaction, and performance. Education level significantly influenced both job satisfaction and performance. Achievement motivation demonstrated strong positive effects on job satisfaction and performance. Job satisfaction partially mediated the relationships between education level and performance, and between achievement motivation and performance. The findings emphasize the importance of developing educational pathways and motivational programs while fostering job satisfaction to enhance nursing performance in hospital settings.